Exploring Dysphemia Sociolinguistics Analysis in Youtube News Sean ''Diddy'' Combs Seen on Video Assaulting Cassie Ventura in 2016 - Syadid , Azizah; Manurung , Elyana Feronica; Hutajulu , Laura Nathania; Sinabutar, Rahel Raphita (Universitas Negeri Medan, 2024)
The use of unique language plays an important role in the media, especially for journalistic businesses such as newspapers. As a strategy to develop a journalistic business, many media are trying hard to attract readers' attention, one of which is the use of dysphemism. This research aims to determine the types of dysphemism contained in three news broadcasting channels via YouTube, namely, CNN, CBS Chicago, and KTSM 9 News regarding the case of ''Sean “Diddy” Combs allegedly attacking and molesting Cassie)''. This research uses qualitative methods using data obtained from the latest news broadcasts on YouTube regarding the P. Diddy case. Data were analyzed and categorized based on the types of dysphemism proposed by Warren (1992). Of the 10 types of dysphemism, 2 data were found for the type of dysphemism (nicknames and expletives), then (taboo terms used as insults) also found 2 data, then (swearing and indecent swearing) also found 2 data. Therefore, this research found 7 types of 8 types of dysphemism according to Warren (1992), in the case of ''Sean “Diddy” Combs who is suspected of having assaulted and abused Cassie)'' on three news broadcasting channels via YouTube, namely CNN, CBS Chicago, and KTSM 9 News.